2012
DOI: 10.1021/nn305486x
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals Epitaxial Growth of Graphene on Sapphire by Chemical Vapor Deposition without a Metal Catalyst

Abstract: van der Waals epitaxial growth of graphene on c-plane (0001) sapphire by CVD without a metal catalyst is presented. The effects of CH(4) partial pressure, growth temperature, and H(2)/CH(4) ratio were investigated and growth conditions optimized. The formation of monolayer graphene was shown by Raman spectroscopy, optical transmission, grazing incidence X-ray diffraction (GIXRD), and low voltage transmission electron microscopy (LVTEM). Electrical analysis revealed that a room temperature Hall mobility above 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
203
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(220 citation statements)
references
References 55 publications
10
203
2
1
Order By: Relevance
“…Without a metal catalyst, graphene growth requires higher temperature. Several pioneering studies toward direct growth of graphene on dielectric substrates have been reported, which need higher temperature in the range from 1100 to 1650 °C 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…Without a metal catalyst, graphene growth requires higher temperature. Several pioneering studies toward direct growth of graphene on dielectric substrates have been reported, which need higher temperature in the range from 1100 to 1650 °C 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…Graphene (an individual sheet of sp 2 hybridized carbon) can be produced by bottom-up approaches, that include epitaxial growth techniques, polymerization of molecules [1][2][3], or top-down methods consisting of delaminating graphite crystals [4]. However, the latter method could result in different graphene-like materials including pristine graphene (PG), produced through liquid phase exfoliation [5,6], and graphene oxide (GO), synthesized by chemical intercalation and the subsequent oxidation of graphitic materials (e.g.…”
Section: Introductionmentioning
confidence: 99%